Papers on the 1962 election : fifteen papers on the Canadian general election of 1962 - Meisel, John (University of Toronto Press, 1964)
The essays included in this volume do not follow any one theme, nor are they given unity by a shared frame of reference. Each author dealt with some aspect of the 1962 election without any concern with what was being attempted by the others.
Fifteen papers on the Canadian general election of 1962.
Mimeographed.
Reprinted in 2018.
Keywords: Canada. -- Parliament -- Elections.; Canada. -- Parliament; Elections -- Canada.; Élections -- Canada.; POLITICAL SCIENCE -- Political Process -- Elections.; POLITICAL SCIENCE -- Political Process -- General.; Elections; Political science; Canada